Long-term effects of the use of a sound masking system in open-plan offices: A field study. (15th January 2020) - Lenne, Lucas; Chevret, Patrick; Marchand, Julien
Abstract: Noise in open-plan offices, and more specifically conversational noise, is a major source of annoyance for employees. The principle of sound masking consists in artificially increasing the background noise in the office, which leads to a decrease in speech intelligibility and therefore a reduction in acoustic annoyance. Nevertheless, the arguments in favour of this technology are based on short-term laboratory studies, whose lack of representativeness limits the application of their conclusions in real open-plan offices. This justifies the present study, which aims to evaluate, in situ and over the long term, the effectiveness of a sound masking system that meets the main scientific and normative recommendations (for example, a masking level below 45 dB(A) and a spectrum with a slope of approximately − 5 dB per octave). Such a sound masking system was installed for several months in an office of a major French banking company. The experiment spanned 26 weeks, 14 of which corresponded to nominal operation of the masking system. The protocol was based on subjective measurements using questionnaires on perceived fatigue, mental workload and perception of the soundscape. The study did not reveal any significant improvement in the assessed psychological factors nor in annoyance caused by office noise. On the contrary, it showed an increase in annoyance caused by noise from office equipment. This highlights the fact that a masking level of 45 dB(A) might already be too high. The results therefore suggest that, in real conditions, a masking system, even if it is used according to specifications that seem to be agreed upon, is not a turnkey solution to the problem of noise in open-plan offices. It is recommended that the installation of these systems be preceded by a holistic analysis of the office: acoustic quality of the room, layout of the workstations and the activities that take place there.